Hydrothermally Synthesized WS2-QDs/Si (0-D/3-D) Vertical Heterojunction for an Efficient Wide Spectral (UV-Vis-NIR) Photodetection - Goswami Y.P.; Gupta P.K.; Pandey A. (My University, 2025)
High-performance broadband photodetectors (PDs) based on transition metal dichalcogenides (TMDs) materials are highly desired for cutting-edge optoelectronics to address the issue of the complexity involved with conventional materials. Despite the reports of the fabrication of broadband PDs based on TMDs, the challenge of employing a less complicated and low-cost fabrication process without compromising performance still needs to be addressed. Hence, the present article reports the fabrication of an economical, facile, water-soluble (nontoxic), and low-temperature operated hydrothermally synthesized WS2-quantum dots (QDs)/Si vertical heterojunction-based broadband PD. The fabricated PD demonstrated to operate at a broad spectrum ranging from 365 to 950 nm (UV-Vis-NIR) and showed a peak responsivity value of 90.21 A / W, external quantum efficiency (EQE) of 30648.55%, and detectivity of 2.08× 1014 Jones at 365 nm. The PD also demonstrated a fast photoresponse speed with a rise and fall time of 44.3 and 39.2 ms, respectively. © 1963-2012 IEEE.